ANALISIS HUBUNGAN FUNDAMENTAL LALU LINTAS BERBASIS SMP DENGAN MODEL GREENSHIELDS - Isra Yanuar Giu; Juang Akbardin; Erna Krisnanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
Traffic flow characteristics are commonly described through the relationship among traffic volume, speed, and density. On roads with mixed traffic conditions, particularly those dominated by motorcycles, the use of Passenger Car Units (PCU) is considered more representative for analyzing traffic performance. This study aimed to analyze the fundamental relationships among traffic volume, speed, and density based on PCU using the Greenshields model on Jalan Raya Mulya Sari, a two-lane two-way undivided road (2/2 UD). Field surveys were conducted on September 2, 2025, using a 5-minute observation interval. Traffic volume data were collected through manual traffic counts and converted into PCU based on the Indonesian Highway Capacity Guidelines (PKJI) 2023, while vehicle speeds were measured using a speed gun and converted into space mean speed. Traffic density was calculated from the relationship between traffic volume and speed. The analysis employed linear regression to establish the Greenshields speed-density model and derive other fundamental traffic relationships. The results showed that the speed-density relationship followed a negative linear pattern. The regression equation for the Junti direction was v = -1.43k + 49.18, while for the Balongan direction it was v = -0.98k + 42.92. The free-flow speeds were 49.18 km/h and 42.92 km/h, respectively. The maximum traffic capacities were estimated at 422.87 PCU/h for the Junti direction and 469.97 PCU/h for the Balongan direction. These findings indicate that the Greenshields model is capable of describing the fundamental traffic flow characteristics of mixed traffic conditions and can be used as a basis for evaluating road performance. Keywords: Greenshields model, Passenger car unit, Traffic density, Traffic volume, Vehicle speed